Infusing Islamic Values Into Reading Module For Islamic Senior High School Students - Martina, Feny; Mustafa, M. Ibnu; Jasrial, Dedi; Rahmawati, Liza; Rahmanina, Lisa (International Journal of Language Pedagogy, 2025)
English reading modules designed to meet the needs of the students at madrasahs are relatively limited. Therefore, this development study reported on the designing process of an English reading module for grade X students of Islamic senior high school through ADDIE framework. This study was conducted through the phases of analysis, design, development, implementation, and evaluation. The participants were 67 students and three English teachers from 9 Islamic senior high schools in Bengkulu City and three module validators. The instruments were subject-expert, student, and teacher questionnaires. The findings on need analyses revealed the students’ and teachers’ expectations on English reading modules containing Islamic values. As a follow-up, a reading module consisting of ten chapters with religious topics in genre-based texts were designed. The evaluation of the module demonstrated that from a 1.0 to 5.0 scale, the module received a score of 4.0 (categorized as good) by the media expert, 4.2 (categorized as excellent) by content and a language expert, 4.1 (categorized as good) by the three English teachers, and 4.3 (categorized as excellent) in a small group evaluation. To conclude, the English reading module is feasible for classroom use. The implication and recommendations for education stakeholders and future researchers are provided.